Let's solve the equation step by step, providing justifications for each action. The equation to solve is:
\[ 2(x+8) = 2x + 8 \]
Step 1: Distribute the left side using the Distributive Property.
\[ 2(x+8) = 2 \cdot x + 2 \cdot 8 \rightarrow 2x + 16 \]
This gives us:
\[ 2x + 16 = 2x + 8 \]
Step 2: Simplify the equation to isolate the terms on one side. Subtract \( 2x \) from both sides.
\[ 2x + 16 - 2x = 2x + 8 - 2x \rightarrow 16 = 8 \]
Now we have a contradiction (16 = 8), indicating that there is no solution.
Summary:
- Step 1: Distributive Property to get \( 2x + 16 = 2x + 8 \)
- Step 2: Simplified equation to \( 16 = 8 \)
For this equation, there is/are: no solution.